Participatory Action Research to Strengthen Al-Qur’an–Hadith Teachers’ Competence in Developing TP–ATP–KKTP for Phase A in an Indonesian Madrasah - Basuki Basuki; Sugiyar Sugiyar; Muhamad Asvin Andur Rohman; Abdah Munfaridatus Sholihah (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study was motivated by preliminary findings indicating that 25 of 35 Al-Qur’an–Hadith teachers at MI Ma’arif Ponorogo experienced difficulties in formulating Learning Objectives (TP), Learning Objective Sequences (ATP), and Learning Objective Achievement Criteria (KKTP) in alignment with the Regulation of the Director General of Islamic Education Number 3302 of 2024. These challenges highlight the need for structured and contextualized professional support in curriculum development.A Participatory Action Research (PAR) design was employed, consisting of three iterative cycles of planning, action, observation, and reflection. Data were collected through observations, interviews, and document analysis, and analyzed qualitatively to examine changes in teachers’ understanding, skills, and professional confidence throughout the intervention.The findings indicate that the PAR-based intervention significantly improved teachers’ competence in developing curriculum components. The formulated TP achieved a high feasibility level (mean score 21.8/24), demonstrating strong alignment with Learning Outcomes (CP) and developmental appropriateness. The ATP reflected coherent and progressive sequencing consistent with Outcome-Based Education and backward design principles. The KKTP attained a high feasibility score (30/32), indicating clear, measurable, and authentic assessment criteria aligned with TP and ATP.The study demonstrates that PAR-based mentoring effectively enhances teachers’ curriculum development competence and operationalizes Outcome-Based Education and Understanding by Design principles. These findings suggest that the approach offers a practical and replicable model for strengthening curriculum implementation within the Merdeka Curriculum framework, although broader application across diverse contexts warrants further investigation.